Hand hygiene adherence among Iranian nurses: A systematic review and meta-analysis - Bijan Nouri; Mohammad Hajizadeh; Kaveh Bahmanpour; Mahsa Sadafi; Satar Rezaei; Sina Valiee (Tehran University of Medical Sciences, 2020)
Background & Aim: Adherence of nurses to hand hygiene is important for the prevention of healthcare-associated infections. This study aims to systematically review the existing studies that assess Iranian nurses' adherence to hand hygiene and estimate their amount with meta-analysis. Methods & Materials: We performed a systematic search for peer-reviewed journals published from 2005 to 2018. The systematic search was conducted using both international (Google Scholar, PubMed, SCOPUS, and Web of Sciences) and Iranian databases (Scientific Information Database, IranMedex, Magiran, and MedLib). The search was carried out using a combination of the following terms: "adherence", "compliance", "hand hygiene", "nurse", "Iran", "nursing practice", "nursing", and "guidelines". The combinations of these words with Boolean operators like 'AND', 'OR' and 'NOT' were used. Results:  A total of 22 articles were used in the final analyses. The pooled proportion of hand hygiene adherence was 40.5 percent [95% confidence interval [CI]: 31.1-49.8]. Sensitivity analysis confirmed that the overall estimated pooled proportion of hand hygiene adherence did not vary significantly with the elimination of any of the 22 studies, observer or self-reported hand hygiene, instrument of measurement, unit of measurements, sample size, and time. Conclusion: The level of adherence of Iranian nurses to hand hygiene can potentially increase the chance of healthcare-associated infections and put patients and nurses at risk. Hospital and nursing managers should take practical steps to investigate factors contributing to the failure of hand hygiene adherence among nursing staff. They should ensure the continuous implementation of hand hygiene improvement strategy.